ANZAC- “coined out of material more precious than gold”: a look at how the Australian home front understood the Gallipoli campaign - Young, Samuel (Kansas State University, 2019)
This thesis will examine the home front of Australia during the Gallipoli campaign of 1915 in order to better understand how Australians conceived of the battle. It argues that individuals within the office of the prime minister self-consciously interpreted the battle in an attempt to establish a uniform national identity that was separate from British imperialism. It also argues that the campaign reinforced prewar gender roles for men and women. Historians have largely ignored the Australian home front during World War I and the immediate postwar period, focusing instead on how Gallipoli has been memorialized over time or on traditional military aspects of the campaign. Analyzing such themes as gender, identity, and race brings questions of citizenship and male and female gender roles into a perspective not yet adequately explored in historical literature. Applying these perspectives to the subject of Australia and Gallipoli, helps us to understand that the campaign was far more than merely a military engagement. It was a social experience that enabled the executive powers of the Australian government the ability to formulate a national identity and restructure society into the image it desired.
Keywords: Australia; Gallipoli; Gender; Identity; Anzac